2005
DOI: 10.1088/0953-2048/18/6/l03
|View full text |Cite
|
Sign up to set email alerts
|

A class of high-TcY Ba2Cu3O7−xgrain boundary junctions with high-IcRnproducts

Abstract: The properties of symmetric 24 • and asymmetric 45 • [100] tilt YBa 2 Cu 3 O 7−x bicrystal grain boundary junctions (GBJs) have been extensively investigated. A large number of junctions, with dimensions ranging from 2 to 20 µm, have been fabricated and characterized at 4.2 K. Experimental data have been compared with [001] tilt bicrystal and [100] tilt biepitaxial YBa 2 Cu 3 O 7−x junctions. [100] GBJs show high I c R n products in the range 5-10 mV at T = 4.2 K, these being slightly sensitive to the critical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
26
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 31 publications
8
26
0
Order By: Relevance
“…This phenomenological result, together with a linear relationship between the critical current density and the specific resistance values, make it reasonable to describe these junctions in a tunnel regime rather than in the filamentary framework. 9 Nevertheless, more structural and chemical studies for this substrate geometry are necessary to corroborate such results.…”
Section: B / T Ratio: Comparison Between 24°[001] Symmetric and 45°[mentioning
confidence: 95%
See 2 more Smart Citations
“…This phenomenological result, together with a linear relationship between the critical current density and the specific resistance values, make it reasonable to describe these junctions in a tunnel regime rather than in the filamentary framework. 9 Nevertheless, more structural and chemical studies for this substrate geometry are necessary to corroborate such results.…”
Section: B / T Ratio: Comparison Between 24°[001] Symmetric and 45°[mentioning
confidence: 95%
“…Then, only in a limited number of cases the I -V curves are well described by the resistively shunted junction model (RSJ model). 9 Nevertheless, because of the presence of hysteresis in most of them, we consider that a calculus of the C / A ratio in terms of the ␤ C parameter could be also appropriated. Tarte et al 23,27 found that the capacitance calculated from the Fiske resonance correlates well with that determined from the hysteresis measurements, but the analysis has mainly been performed on YBCO 24°and 36°[001] symmetrical JJs.…”
Section: B / T Ratio: Comparison Between 24°[001] Symmetric and 45°[mentioning
confidence: 99%
See 1 more Smart Citation
“…For high-T C SQUIDs the simple rule I C R N = const valid for low-T C SQUIDs does not apply in the case of interferometers based on the symmetric bicrystal c-axis [001] devices. In such ASQUIDs, I C R N is proportional to the critical current density J C at low values and stays roughly constant at high-J C values and changing one single parameter is now possible [6].…”
Section: Discussionmentioning
confidence: 99%
“…1b) have been fabri cated [16][17][18][19][20][21][22][23][24][25] with an order of magnitude lower GB meandering and up to a threefold increase of the I c R n values [16][17][18][19]. A complete antiphase correlation between low frequency fluctuations of the resistance R n and the critical current I c has been observed in these junctions, thus showing that both quasiparticles and Cooper pairs flow directly through the same regions of the barrier [24].…”
mentioning
confidence: 99%